Information content of a new observable: The case of the nuclear neutron skin - Reinhard, Paul-Gerhard; Nazarewicz, W. (Physical Review C - Nuclear Physics, 2010)
We address two questions pertaining to the uniqueness and usefulness of a new observable: (i) Considering the current theoretical knowledge, what novel information does new measurement bring in? (ii) How can new data reduce uncertainties of current theoretical models? We illustrate these points by studying the radius of the neutron distribution of a heavy nucleus, a quantity related to the equation of state for neutron matter that determines properties of nuclei and neutron stars. By systematically varying the parameters of two theoretical models and studying the resulting confidence ellipsoid, we quantify the relationships between the neutron skin and various properties of finite nuclei and infinite nuclear matter. Using the covariance analysis, we identify observables and pseudo-observables that correlate, and do not correlate, with the neutron skin. By adding the information on the neutron radius to the pool of observables determining the energy functional, we show how precise experimental determination of the neutron radius in Pb208 would reduce theoretical uncertainties on the neutron matter equation of state. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2023-07-24